The Function and Values of the Kompolan Sabellesen Tradition in Madurese Society - M. Salman Al Farisi (Warisan: Journal of History and Cultural Heritage, 2024)
The Kompolan Sabellesen tradition is one of the many Islamic communal traditions in Madura that serve as a medium for fostering social functions and values within the community. This study aims to examine the functions and Islamic values embedded in the Kompolan Sabellesen tradition, particularly in strengthening social bonds, ukhuwah Islamiyah (Islamic brotherhood), and social solidarity among the Madurese people. Employing a qualitative method with an anthropological approach, this research utilizes both textual sources—such as books and journals—and oral sources. Data analysis is conducted using symbolic interpretive theory. Fieldwork was carried out in several districts in Madura, including Sumenep, Pamekasan, Sampang, and Bangkalan. The findings reveal that this tradition plays a crucial role in shaping socio-religious dynamics within the Madurese community, reinforcing communal identity, and fostering harmonious social interactions. The tradition is not only a cultural heritage but also a vital mechanism for maintaining religious and social cohesion in Madura.